2016
DOI: 10.1037/dev0000113
|View full text |Cite
|
Sign up to set email alerts
|

Aiming to complete the matrix: Eye-movement analysis of processing strategies in children’s relational thinking.

Abstract: The present study examines 5- to 8-year-old children's relation reasoning in solving matrix completion tasks. This study incorporates a componential analysis, an eye-tracking method, and a microgenetic approach, which together allow an investigation of the cognitive processing strategies involved in the development and learning of children's relational thinking. Developmental differences in problem-solving performance were largely due to deficiencies in engaging the processing strategies that are hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 53 publications
4
48
0
Order By: Relevance
“…Clarifying aspects of brain circuitry by illustrating the complex interplay between vision and cognition, 62 eye movement measurements are actively performed in interdisciplinary laboratories that integrate contributions from psychology, neuroscience, economy, philosophy and computer science. A vast number of efficient and well‐grounded behavioral experimental paradigms have been generated regarding sincerity, 63 magic‐tricks, 64, 65 judgmental tasks, 66–71 moral dilemma, 72 reading, 73–76 visual search, 77–79 gambling, 80 daily‐life activities, 81–86 problem‐solving, 39, 87–89 learning 90 and discrete choice in clinical decision‐making 91 . Vision science becomes actively adopted in neuromarketing, aiming to reveal valuable information about consumers’ decisions, as well as answer the question of how to hack the consumer's internal ‘purchase button’ 92–96 …”
Section: Vision Science As a New Practicementioning
confidence: 99%
“…Clarifying aspects of brain circuitry by illustrating the complex interplay between vision and cognition, 62 eye movement measurements are actively performed in interdisciplinary laboratories that integrate contributions from psychology, neuroscience, economy, philosophy and computer science. A vast number of efficient and well‐grounded behavioral experimental paradigms have been generated regarding sincerity, 63 magic‐tricks, 64, 65 judgmental tasks, 66–71 moral dilemma, 72 reading, 73–76 visual search, 77–79 gambling, 80 daily‐life activities, 81–86 problem‐solving, 39, 87–89 learning 90 and discrete choice in clinical decision‐making 91 . Vision science becomes actively adopted in neuromarketing, aiming to reveal valuable information about consumers’ decisions, as well as answer the question of how to hack the consumer's internal ‘purchase button’ 92–96 …”
Section: Vision Science As a New Practicementioning
confidence: 99%
“…For example, Arendasy and Sommer [8] showed that when participants rely on a response elimination strategy, the test’s Gf loading is reduced. Chen, Honomichl, Kennedy, and Tan [9]’s cross-sectional and microgenetic study indicated that children’s thinking becomes increasingly relational with age and experience. However, it also suggested that many children tend to underperform, insofar as minor changes in the administration procedure (e.g., verbal feedback) can help them implement more efficient strategies.…”
Section: Introductionmentioning
confidence: 99%
“…To examine processing strategies, we computed the frequency of saccade paths between target and relational locations and saccade paths between target and non-relational locations using a custom-made Scanpath MATLAB toolbox. We reasoned that saccade paths between target and relational locations represented item comparison and relational encoding ( Chen et al, 2016 ). These fixation-based and saccade-based measures have been widely used in analogical reasoning research using similar paradigms and stimuli ( Demarais and Cohen, 1998 ; Gordon and Moser, 2007 ; Thibaut et al, 2011 ; Chen et al, 2016 ; Thibaut and French, 2016 ), and in other research areas with children diagnosed with ASD ( Yi et al, 2013 , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further details of these measures are provided in the material and methods section. These two eye-movement measures have been widely used in analogical reasoning research using similar paradigms and stimuli ( Demarais and Cohen, 1998 ; Gordon and Moser, 2007 ; Thibaut et al, 2011 ; Chen et al, 2016 ; Thibaut and French, 2016 ; Eckstein et al, 2017 ) and in other research areas with children diagnosed with ASD ( Yi et al, 2013 , 2014 ). We reasoned that if children with ASD are biased toward local features and perceptual similarities, they should spend less time looking at relational locations and show fewer saccade paths between relational locations.…”
Section: Introductionmentioning
confidence: 99%